The Influence of Android Application-Based Education on Adolescent Knowledge Regarding Stunting Prevention in Madrasah Aliyah Amanatul Ummah, Surabaya - Nabilah Antikasari; Domas Nurchandra P; Evi Pratami; Tatarini Ika Pipitcahyani (International Journal of Advanced Health Science and Technology, 2023)
There are different phases in the human life cycle. at every phase involving human nutritional intake. To analyze the effect of the use of Android media applications on youth's knowledge about stunting prevention. This type of research is Quasi-Experimental with a one-group pre-test post-test research design. The population is 80 teenagers at the Amanatul Ummah Madrasah Aliyah Islamic Boarding School, Surabaya. Samples were taken by purposive sampling of 35 teenagers. The independent variable is the use of the Android application. The dependent variable is knowledge about stunting prevention in young women. The research instrument was a questionnaire with 20 questions about stunting prevention. Methods Univariate and bivariate analysis using the Wilcoxson test. Methods Univariate and bivariate analysis using the Wilcoxson test. The results of the study show that there is a significant increase in knowledge with the result ρ value = 0.001 p <α (0.05). The results of the study show the effect of using educational applications related to Android-based stunting prevention to increase knowledge in young women. So it is recommended that teenagers use educational applications related to Android-based stunting prevention to increase their knowledge about stunting prevention.